Summer is Coming! Join the Game of Timers Competition to Win Epic Prizes. Registration is Open. Game starts Mon July 1st.

 It is currently 19 Jul 2019, 03:24

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If L = (a - b) - c and R = a - (b - c), then L - R =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 56302
If L = (a - b) - c and R = a - (b - c), then L - R =  [#permalink]

### Show Tags

07 Aug 2018, 04:17
00:00

Difficulty:

15% (low)

Question Stats:

68% (00:43) correct 32% (00:50) wrong based on 48 sessions

### HideShow timer Statistics

If $$L = (a - b)- c$$ and $$R = a - (b - c)$$, then $$L - R =$$

(A) 2b

(B) 2c

(C) 0

(D) -2b

(E) -2c

_________________
Manager
Joined: 22 Jun 2017
Posts: 71
Location: Brazil
GMAT 1: 600 Q48 V25
GPA: 3.5
WE: Engineering (Energy and Utilities)
Re: If L = (a - b) - c and R = a - (b - c), then L - R =  [#permalink]

### Show Tags

07 Aug 2018, 05:28
L = a - b - c
R = a - b + c
-R = -a + b - c

Hence, L - R = a - b - c - a + b - c = -2c

Option E
Intern
Joined: 07 Aug 2018
Posts: 1
Re: If L = (a - b) - c and R = a - (b - c), then L - R =  [#permalink]

### Show Tags

07 Aug 2018, 05:35
L-R= a-b-c-a+b-c=-2c

So correct answer is option E.

Posted from my mobile device
Retired Moderator
Joined: 30 Jan 2015
Posts: 805
Location: India
Concentration: Operations, Marketing
GPA: 3.5
Re: If L = (a - b) - c and R = a - (b - c), then L - R =  [#permalink]

### Show Tags

07 Aug 2018, 06:58
L = (a - b)- c = a - b - c
R = a - (b - c) = a - b + c

L - R = a - b - c - (a - b + c) = a - b - c - a + b - c = -2c

Hence, E.
_________________
The few, the fearless !

Thanks
Board of Directors
Status: QA & VA Forum Moderator
Joined: 11 Jun 2011
Posts: 4512
Location: India
GPA: 3.5
If L = (a - b) - c and R = a - (b - c), then L - R =  [#permalink]

### Show Tags

07 Aug 2018, 07:05
Bunuel wrote:
If $$L = (a - b)- c$$ and $$R = a - (b - c)$$, then $$L - R =$$

(A) 2b

(B) 2c

(C) 0

(D) -2b

(E) -2c

$$L = a - b - c$$

$$R = a - b + c$$

So, $$L - R = (a - b - c ) - ( a - b + c )$$

Or, $$L - R = a - b - c - a + b - c$$

Or, $$L - R = - 2c$$, Answer must be (E)
_________________
Thanks and Regards

Abhishek....

PLEASE FOLLOW THE RULES FOR POSTING IN QA AND VA FORUM AND USE SEARCH FUNCTION BEFORE POSTING NEW QUESTIONS

How to use Search Function in GMAT Club | Rules for Posting in QA forum | Writing Mathematical Formulas |Rules for Posting in VA forum | Request Expert's Reply ( VA Forum Only )
Director
Joined: 04 Sep 2015
Posts: 632
Location: India
WE: Information Technology (Computer Software)
Re: If L = (a - b) - c and R = a - (b - c), then L - R =  [#permalink]

### Show Tags

09 Aug 2018, 03:59
L=a−b−c

R=a−b+c

So,
L−R=(a−b−c)−(a−b+c)

Or,
L−R=a−b−c−a+b−c

Or,
L−R=−2c
Senior Manager
Status: Manager
Joined: 02 Nov 2018
Posts: 283
If L=(a-b)-c and R=a-(b-c), then L - R =  [#permalink]

### Show Tags

11 Mar 2019, 01:26
Given that,
L=(a-b)-c or a-b+c
R=a-(b-c) or a-b+c
So L-R = 0
because both value are same
_________________
Give a kudos if u find my post helpful. kudos motivates active discussions

Manager
Joined: 09 Mar 2018
Posts: 56
Location: India
Schools: CBS Deferred "24
Re: If L=(a-b)-c and R=a-(b-c), then L - R =  [#permalink]

### Show Tags

11 Mar 2019, 02:55
L=(a-b)-c
we can write this as a-b-c ( removing the bracket won't alter the sign)

R=a-(b-c)
we can write this as a-b+c

L-R= a-b-c-(a-b+c)
which equals : a-b-c-a+b-c

so we get : -2C
Intern
Joined: 10 Feb 2019
Posts: 1
Re: If L=(a-b)-c and R=a-(b-c), then L - R =  [#permalink]

### Show Tags

11 Mar 2019, 09:13
L-R=a-b-c-a+b-c
i.e. -2c
e-GMAT Representative
Joined: 04 Jan 2015
Posts: 2943
Re: If L=(a-b)-c and R=a-(b-c), then L - R =  [#permalink]

### Show Tags

11 Mar 2019, 21:24

Solution

Given:
• L = (a – b) – c = a – b – c
• R = a – (b – c) = a – b + c

To find:
• The value of L – R

Approach and Working:
As we already have the simplified expressions of both L and R, we can get the value of L – R as follows:
• L – R = (a – b – c) – (a – b + c) = a – b – c – a + b – c = a – a – b + b – c – c = - 2c

Hence, the correct answer is option E.

_________________
Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 6925
Location: United States (CA)
Re: If L=(a-b)-c and R=a-(b-c), then L - R =  [#permalink]

### Show Tags

14 Mar 2019, 07:22
Bunuel wrote:
If L=(a-b)-c and R=a-(b-c), then L - R =

A. 2b
B. 2c
C. 0
D. -2b
E. -2c

L - R is:

(a - b) - c - [a - (b - c)]

a - b - c - [a - b + c]

a - b - c - a + b - c = -2c

_________________

# Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com
122 Reviews

5-star rated online GMAT quant
self study course

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

Re: If L=(a-b)-c and R=a-(b-c), then L - R =   [#permalink] 14 Mar 2019, 07:22
Display posts from previous: Sort by